Detection of mind wandering using EEG signals - Tasika, Nadia Jebin; Alam, Salwa; Rimo, Mohsena Begum; Haque, Mohtasim Al; Haque, Mohammad Hasibul (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2020.